Engineering nanoparticle synthesis using microbial factories. Issue 1 (11th July 2017) - Pasula, Rupali Reddy; Lim, Sierin
Abstract : Biologically engineered entities have enabled discoveries in the past decade and a half, spanning from novel routes for the syntheses of drugs and value‐added products to carbon capture. The precise cellular re‐programming has extended to the production of nanomaterials owing to their ever‐growing demand. The primary advantage of the biological nanoparticle synthesis is the eco‐friendly approach performed at ambient temperature and pressure, where the usage of harsh chemical stabilisers and capping agents is eliminated, providing ease of handling and downstream processing. Although the techniques hold great promise, many short comings hamper their scalability; thus, rendering them unsuitable for industrial applications. A fundamental understanding of the underlying mechanisms which involve various enzymes of different metabolic pathways is most crucial in surmounting these impending blocks leading to successfully engineered systems which can be tuned in accordance with the goals of specific applications. This mini review highlights the recent developments in nanoparticle synthesis that employ the use of microbial reaction vessels with specific emphasis on engineering of these biological entities such as bacteria, yeast, fungi and algae. Also presented are the challenges and future trends in this domain where novel and engineered approaches will be the most consequential.